2011
DOI: 10.1590/s1677-55382011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of a novel ergonomic surgical chair for laparoscopic pelvic surgery

Abstract: Introduction:We present the initial experience of a novel surgical chair for laparoscopic pelvic surgery, the ETHOS TM (Bridge City Surgical, Portland, OR). Materials and Methods:The ETHOS chair has an adjustable saddle height that ranges from 0.89 to 1.22 m high, an overall width of 0.89 m, and a depth of 0.97 m. The open straddle is 0.53 m and fits most OR tables. We performed 7 pelvic laparoscopy cases with the 1 st generation ETHOS TM platform including 2 laparoscopic ureteral reimplantations, 5 laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Although studies have demonstrated some improvement in mental focus and reduction in musculoskeletal pain and fatigue with TSMBs [ 21 , 28 ], complete effectiveness in the long term is yet to be seen. In the case of RAS, an ergonomic operating chair may help improve comfort by maintaining a correct posture while operating [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated some improvement in mental focus and reduction in musculoskeletal pain and fatigue with TSMBs [ 21 , 28 ], complete effectiveness in the long term is yet to be seen. In the case of RAS, an ergonomic operating chair may help improve comfort by maintaining a correct posture while operating [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical feasibility was initially proved, by Kim et al, in a limited number of laparoscopic pelvic urological procedures. 9 Rassweiler et al 10 using also the ETHOS prototype extended its clinical evaluation by comparing 53 consecutive ETHOS-assisted laparoscopic radical prostatectomies with 53 robotically assisted radical prostatectomies and 53 conventional laparoscopic radical prostatectomies, in a matched-paired analysis, according to different ergonomic parameters. The questionnaires proved the superiority of robotic pelvic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the negative effects of a nonergonomic posture, the chronic limited body movement without weight shifting, and the nonergonomic design of different surgical instruments, became more apparent, 8 especially when performing complex pelvic procedures such as a laparoscopic radical prostatectomy. 7 Based on previously published preliminary clinical experience using the prototype, 9,10 we present the experimental evaluation of the second-generation operating chair (ETHOSÔ). This platform is designed to improve the ergonomics of laparoscopic procedures, by comparing it with the two different conventional laparoscopic positions during laparoscopic suturing and vesicourethral anastomosis, in a training room setting.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is mainly associated with pelvic laparoscopy (24). Half of the expert sessions and half of the novice sessions were done in line (COV1), as schematically depicted in Figure 5a and b.…”
Section: Discussionmentioning
confidence: 99%